Lenalidomide versus lenalidomide + dexamethasone prolonged treatment after second‐line lenalidomide + dexamethasone induction in multiple myeloma - Johan Lund; Astrid Gruber; Birgitta Lauri; Adil Doganay Duru; Cecilie Blimark; Agneta Swedin; Markus Hansson; Karin Forsberg; Lucia Ahlberg; Conny Carlsson; Anders Waage; Peter Gimsing; et al. (Cancer Medicine)
Abstract Lenalidomide (Len) plus dexamethasone (Dex) is approved for the treatment of relapsed or refractory multiple myeloma (RRMM). It is possible that single‐agent Len may be effective as prolonged treatment regimen in RRMM once patients demonstrate an initial response to Len+Dex induction. Patients with RRMM who responded to first‐line Len+Dex in an observational study (NCT01430546) received up to 24 cycles of either Len (25 mg/day) or Len+Dex (25 mg/day and 40 mg/week) as prolonged treatment in a subsequent phase 2 clinical trial (NCT01450215). In the observational study (N = 133), median time to response was 1.7 (range 0.6–9.6) months. A complete response to all treatments received in both studies was observed in 11% of patients; very good partial response and partial response rates were 31% and 38%, respectively. Corresponding response rates in the subgroup of patients who did not enter the phase 2 trial (n = 71) were 3%, 18%, and 39%, respectively. Rates of disease progression at 2 years in the phase 2 trial were 47% versus 31% for Len versus Len+Dex (P = 0.14). After 36 months median follow‐up in surviving patients, median time to progression was not reached with Len+Dex and was 24.9 months (95% confidence interval 12.5–not calculable, P < 0.001) with Len. Three‐year OS among the total observational study population was 61% (95% CI, 52–69%). The corresponding rate among patients who entered the phase 2 clinical trial was 73% (95% CI, 60–83%) and was significantly lower among those patients who achieved ≥PR but did not proceed into the phase 2 trial (55%; P = 0.01). In the phase 2 trial, OS was 73% in both treatment arms (P = 0.70). Neutropenia and thrombocytopenia were more common with prolonged (phase 2 trial) versus short‐term (observational study) Len administration but remained manageable. Prolonged treatment with Len with or without Dex provides sustained, clinically relevant responses and demonstrates an acceptable safety profile.